Seizure as an instrument for searching evidence in crimes against the public administration - Fernandez Vasquez, Marcelo Alejandro (2024)
Seizure, by virtue of Plenary Agreement No. 05-2010/-CJ-116 of the Supreme Court of Justice of Peru, is divided into: (a) seizure for evidentiary or instrumental purposes (art. 218 of the Criminal Procedure Code); (b) seizure for coercive or precautionary purposes (art. 316 of the Criminal Procedure Code). In tax investigations for crimes against the public administration, it is vitally important to know how to use and distinguish both forms of seizure, since each tax case has different facts and particularities. This research article will analyze and delve into seizure for evidentiary purposes as an effective instrument in tax investigations for crimes against the public administration, developing the procedure to follow and the main problematic scenarios that may arise in its use; for example, the distinction between a voluntary delivery of a seizure, if first of all seized property or element its sealing and chain of custody proceed, judicial confirmation in case of voluntary delivery of public assets or documents, the procedure for seizure of non-private documents and among others more aspects.